Knowledge management and financial performance of Malaysian public higher education enterprise risk management as a mediator - Abdul Rauf, Ummu Ajirah (2022)
Knowledge management (KM) in public higher education (PHE) helps them in acquiring the information on income generation, identifying and analyzing the risk across the organization and lead to the successful of enterprise risk management (ERM) implementation. ERM in PHE is crucial as it is aimed at mitigating the multidimensional risks that faced by PHE after been granted an autonomous status as well as enhancing their financial performance. Nevertheless, they are still far behind the corporate sector in implementing ERM as they have limited knowledge towards risk management. Therefore, PHE must have a good KM to establish understanding towards the concepts of ERM as well as helps them to enhance the knowledge on income generation, thus lead to the better financial performance. Based on the arguments, it indicated ERM are able to be a mediator between KM and financial performance of PHE. The link between ERM and performance have been widely discussed, however, it was commonly explores on other industries and majority of it was investigated among developed countries which resulting to diverse conclusions. There is also limited research on KM and performance of Malaysian PHE mediated by ERM implementation. Therefore, this research is crucial to fill the gap as it focuses on uncovering the factors under KM that encourage the ERM implementation and how ERM implementation as a mediator can enhance the financial performance of Malaysian PHE. Using the Open System Theory as the theoretical foundation, this research has developed a model on the mediating effect of ERM implementation, by utilizing the KM components (KMC) which include work coordination, communication, interaction information system, knowledge sharing, management information system functionality, intranet quality, information system integration and network capability that can enhance the financial performance of Malaysian PHE. Data were collected from Malaysian PHE using a cross sectional design and multistage sampling method (purposive, stratified and census). A total of 210 usable questionnaires were collected by online survey and analysed with Covariance-Based SEM (CB-SEM). 14 out of the 25 hypotheses were supported; work coordination, management information system functionality, intranet quality, information system integration and network capability have direct influence with financial performance of Malaysian PHE, while work coordination, communication, intranet quality and network capability positively influenced the ERM implementation. Moreover, the significant mediating effect of ERM implementation has shown indirectly its strong influence with the performance of Malaysian PHE. This research makes several theoretical contributions and provides further insights on the KMC and impacts of ERM implementation in Malaysia. From the managerial viewpoint, this research provides a valid and applicable framework to encourage the ERM implementation in Malaysian PHE. Besides, practical contribution indicates that, by implementing ERM, Malaysian PHE will have better financial performance in terms of income generation. The important implications of this research to the Ministry of Higher Education (MOHE), policy makers, academics and risk practitioners are identified through the enhanced knowledge towards the concept and importance of ERM to encourage the implementation, as well as long term impact of ERM towards achieving better financial performance. There is also a need for a revisit of the policy instrument as to realign it with the current ERM implementation and provide supportive policies that will improve the financial performance of Malaysian PHE.